The novel «Journey to the west» and changes after distribution abroat (Journal of Oriental Studies, 2018)
“Journey to the west” is one of the largest chinese classical compositions, the mythological roman.The novel tells the story about monk which from the Tang dynasty with his companions’s journey onthe Silk Road to India for Buddhist with sutras. The novel, written in the mid 17th century, and widelydistributed throughout the world and has been translated into many languages. In the article, we brieflyfocus on the content of the stories, and the change after the spread in other countries of the world